2020
DOI: 10.17305/bjbms.2020.5096
|View full text |Cite
|
Sign up to set email alerts
|

Bionformatics analysis reveals TSPAN1 as a candidate biomarker of progression and prognosis in pancreatic cancer

Abstract: Pancreatic cancer (PCC) is a common malignant tumor of the digestive system that is resistant to traditional treatments and has an overall 5-year survival rate of less than 7%. Transcriptomics research provides reliable biomarkers for diagnosis, prognosis and clinical precision treatment, as well as the identification of molecular targets for the development of drugs to improve patient survival. We sought to identify new biomarkers for PCC by combining transcriptomics and clinical data with current knowledge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Another study has identified TSPAN1 as one of the potential diagnostic markers and was expressed at a high level in PC tissues and cells, which was consistent with our study results [ 19 ]. Ma C et al identified TSPAN1 could be involved in PC progression and act as a critical biomarker for diagnosing and predicting patient survival with PC through weighted gene co-expression network analysis [ 20 ]. Even so, the role of TSPAN1 in the prognosis of PC is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has identified TSPAN1 as one of the potential diagnostic markers and was expressed at a high level in PC tissues and cells, which was consistent with our study results [ 19 ]. Ma C et al identified TSPAN1 could be involved in PC progression and act as a critical biomarker for diagnosing and predicting patient survival with PC through weighted gene co-expression network analysis [ 20 ]. Even so, the role of TSPAN1 in the prognosis of PC is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…TSPAN1 is a transmembrane protein that has been reported to be elevated in many human cancers and to be involved in tumor progression [8][9][10][11][12]. According to our previous RNA-Seq with TSPAN1overexpressing, shTSPAN1 and their corresponding control PANC-1 cells.…”
Section: Fam110a Is An Essential Target Of Tspan1 Pdacmentioning
confidence: 99%
“…Tetraspanin 1 (TSPAN1) is a member of the tetraspanin family, which is a family of small transmembrane proteins. TSPAN1 has been reported to be elevated in many human cancers and to be involved in tumor progression [8][9][10][11][12]. Our previous study has revealed that TSPAN1 is an oncogene that promotes cell proliferation, migration, invasion and tumorigenesis in PDAC [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tetraspanin1 TSPAN-1, NET-1 Intestine, testis Regulation of cell development, activation, growth and motility (Liu et al, 2019;Wang L. et al, 2021). Prognostic role in prostate (Stinnesbeck et al, 2021), pancreatic (Ma C. et al, 2021), and cervical (Wollscheid et al, 2002) cancer Plays an important role in normal bladder epithelial physiology (Wu et al, 1995;Lobban et al, 1998;Ogawa et al, 1999;Hall et al, 2005). Upregulation connected with lung cancer cells (Byun et al, 2020), downregulation enhances apoptosis of bladder carcinoma cells (Zhu et al, 2015) and reduced expression associated with gastric adenocarcinoma (Zheng et al, 2014) Tetraspanin22 TSPAN22, PRPH2, CACD2, rd2, RDS, RP7, Peripherin 2 Retina Essential for retina photoreceptor outer segment disk morphogenesis (Donato et al, 2021) and involved in retinal degeneration (Travis et al, 1991), macular dystrophy (Kumaran et al, 1993;Çavdarli et al, 2020) and retinitis pigmentosa (Kajiwara et al, 1991;Farrar et al, 1992;Jordan et al, 1992; Tetraspanin23 TSPAN23, ROM1, ROM, Retinal outer segment membrane protein 1 Retina Plays a role in rod outer segment (ROS) morphogenesis (Conley et al, 2017).…”
Section: Protein Functionmentioning
confidence: 99%